Using artificial intelligence in research and improvement of the technology of roll forming of bent 3D-type profiles - Babay, Yuriy (National Technical University "Kharkiv Polytechnic Institute", 2025)
The research explores the application of artificial intelligence (AI) to optimize the roll forming process for bent 3D-type profiles. AI-driven algorithms are used to predict deformation behavior, optimize process parameters, and enhance production efficiency. The study aims to improve precision, reduce material waste, and accelerate industrial adoption of advanced roll forming technologies.
Keywords: artificial intelligence; roll forming; bent 3D profiles; optimization; predictive modeling; machine learning; production efficiency